Study of serum insulin and thyroid hormones levels among infertile females in Bangladesh - Bari, Shamima; Begum, Rokeya; Begum, Jesmine Ara; Pravin, Shahana; Begum, Mahmuda; Mahruba, Syeda Nusrat (International Journal of Research in Medical Sciences, 2025)
Background: Infertility affects 8-10% of couples worldwide, with altered insulin and thyroid levels as potential factors. This study examines fasting serum insulin and thyroid hormones in women with primary and secondary infertility. Methods: The study included 100 women, with 50 experiencing primary infertility (Group A) and 50 with secondary infertility (Group B). Age-matched fertile women served as the control group. Data were recorded on a standardized data sheet following written consent. Statistical analysis was performed using unpaired Student’s t-tests with SPSS software, version 12. Results: In this study, the mean fasting serum insulin and TSH levels were significantly higher in infertile women compared to fertile women (p<0.001). Within the infertility group, serum fasting insulin was higher in women with primary infertility than in those with secondary infertility, although this difference was not statistically significant. The mean TSH levels in both infertility groups were significantly elevated compared to the fertile group. Among those with infertility, 28% of women with primary infertility and 24% with secondary infertility had hypothyroidism, while elevated serum insulin levels were observed in 22% and 20% of these groups, respectively. Among the hypothyroid infertile women, 64.2% (9 of 14) with primary infertility and 58.3% (7 of 12) with secondary infertility also had hyperinsulinemia. Conclusions: The study found higher fasting serum insulin and TSH levels in infertile women, often linked to hypothyroidism, menstrual irregularities, and ovulatory dysfunction. It emphasizes the need to assess TSH and insulin levels in infertility evaluations.